Disclosing Australian Newspaper’s Ideologies in Reporting Political News through Social Actor Representations Strategy : CDA Perspective - Surjowati, Ribut (NOBEL: Journal of Literature and Language Teaching, 2020)
This research aims at explaining how and why the Sydney Morning Herald communicates its ideologies in such a way through the social actors represented in news reports. Using Fairclough’s and Van Dijk’s model of CDA and Theo Van Leeuwen’s framework of the representation of social actors, the study found that in terms of assimilation, nomination and categorization, functionalization and identification, and Impersonalization, the newspaper viewed the Indonesian government, army, and military officers as the Out group social actors, and Australian, Papuan activists and those who support Papuan conflict as the In group social actors. These categorizations serve different purposes. Those who are related to the Out groups express a purpose to emphasize their brutality, superiority, and dominance towards the indigenous Papuans. On the other hand, In groups social actors were indicated as peacemakers. These findings signaled Australia’s political ideologies and hidden purposes towards Indonesia. Australia views itself as a liberal country which respects individual freedom; therefore, the government must protect and get justice, and, it is also Australia’s responsibility to give aids to Papuans who are seeking better place as stated in the international law which gives a picture of how this country is concerned towards Indonesia